Evidence mapping of current status, impact, prevention and control measures from rabies research in Bangladesh (2010–2021): a scoping review protocol - Rubyath Binte Hasan; Jinnat Ferdous; Mahfuja Luna; Mosammat Moonkiratul Zannat (BMJ Open)
Introduction Rabies is one of the priority zoonotic diseases in Bangladesh. Though the rabies cases have been reduced over the years due to the mass dog vaccination programme since 2011 throughout the country, it is still a major health problem in Bangladesh with an annual estimated 200 000 animal bite cases and over 2000 human deaths. This article presented a scoping review protocol for published literature on rabies in Bangladesh and believes to create impact in Bangladesh by identifying the research gap and guiding the evidence-informed policy adaptation from its findings in the future which will strongly underscore the elimination of Rabies and reduce preventable mortalities. We will attempt to synthesise evidence descriptively on burden and impact of rabies in human population as well as the awareness level and effective control and preventive measures from the available studies on rabies from 2010 to 2021 in Bangladesh.Methods The scoping review is planned following the Joanna Briggs Institute methodology and the major guiding steps are: defining the research questions, determining the eligibility criteria with population, concept and context strategy, stating the plan for evidence searching, selection and data collection, searching for evidence and selection of literature by the inclusion criteria, data collection, descriptive analysis and presentation of the data and reporting of the findings. Search will be conducted for both published and grey literature in English language. Blinded screening processes will be adapted to prevent bias among reviewers.Ethics and dissemination A scoping review synthesises existing knowledge and does not necessitate ethical approval. Results of this scoping review will be submitted to a journal for publication, presented in relevant conferences and disseminated on social media platforms (eg, Twitter) among the global health stakeholders.